Perbedaan kemampuan pemecahan masalah matematika siswa yang diajar dengan model pembelajaran team assisted individualized dan model pembelajaran contextual teaching and learning di kelas VIII MTS. PAB 1 Helvetia - Ihsania, Cindy Nur Annisa (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to determine the differences in students’ mathematical problem-solving abilities taught by the Team Assisted Individualized learning model and the Contextual Teaching and Learning learning model in class VIII MTs. PAB 1 Helvetia. The population in the study were all students of class VIII MTs. PAB 1 Helvetia with 144 students and the sample is class VIII A and class VIII-B with 72 students. Sampling using the Cluster Random Sampling technique. Data analysis was performed using the t-test statistical formula. The results of this finding indicate :) the ability of students to solve mathematical problems that have been given the treatment of Team Assisted Individualized and Contextual Teaching and Learning increased from before. 2) The average value of students who received Team Assisted Individualized treatment was better, reaching 78,194 from the previous value of 61,111, and so with the average value of being treated by Contextual Teaching and Learning reaching 76,111 from the value before being given treatment that is 57,083. 3) There is a difference in the students’ mathematical problem-solving abilities taught by the Team Assisted Individualized learning model and Contextual Teaching and Learning in class VIII MTs. PAB 1 Helvetia. Namely, the use of Team Assisted Individualized learning models further enhances students’ mathematical problem-solving abilities compared to the Contextual Teaching and Learning model.